Not just about gadgets: Habit, innovation and change in the design of learning technologies. (12th June 2015) - Carmichael, Patrick
While elements of Deleuze's theory, notably the 'geophilosophical' concepts of 'rhizomes', 'smoothness' and 'striation' have been applied to educational technologies, his work on time has, to date, been comparatively neglected by educational theorists. This article explores practices and outcomes of educational technology design in terms of Deleuze's dimensions of time in which habitual practices, trajectories of change and concerns about identities in flux are synthesised into a 'present-becoming'. The article draws on empirical work carried out during a large, funded research project during which teachers, students, technologists and researchers were able to work together for extended periods in order to explore the potential of emerging 'semantic web' and 'linked data' technologies and approaches in higher educational settings ( Ensemble: Semantic Technologies for the Enhancement of Case Based Learning ). Doing learning technology design and development in a way informed by 'Deleuzian' syntheses of time involves conversations not just about creating a technology-rich educational utopia or constantly specifying new 'gadgets', but the troubling of existing pedagogical practices and the multiplication of perspectives and subjectivities. By going beyond notions of 'feature sets', 'use cases' and 'affordances' it provides a richer conceptual framework that helps us understand why some educational technologies are adopted and abandoned, some are creatively appropriated and used in unexpected ways, and others sink without trace. The article concludes with suggestions as to how current conditions in higher education, rather than constraining the development of educational technologies, might provide opportunities for these broader explorations to be initiated.